2006
DOI: 10.1104/pp.106.092320
|View full text |Cite
|
Sign up to set email alerts
|

Repression of theLEAFY COTYLEDON 1/B3Regulatory Network in Plant Embryo Development byVP1/ABSCISIC ACID INSENSITIVE 3-LIKEB3 Genes

Abstract: Plant embryo development is regulated by a network of transcription factors that include LEAFY COTYLEDON 1 (LEC1), LEC1-LIKE (L1L), and B3 domain factors, LEAFY COTYLEDON 2 (LEC2), FUSCA3 (FUS3), and ABSCISIC ACID INSENSITIVE 3 (ABI3) of Arabidopsis (Arabidopsis thaliana). Interactions of these genes result in temporal progression of overlapping B3 gene expression culminating in maturation and desiccation of the seed. Three VP1/ABI3-LIKE (VAL) genes encode B3 proteins that include plant homeodomain-like and CW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
290
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(310 citation statements)
references
References 70 publications
12
290
0
1
Order By: Relevance
“…This phenotype is associated with upregulation of LAFL gene expression, as well as ectopic expression of the stem cell regulators WUSCHEL RELATED HOMEOBOX 5 ( WOX5) , BBM , SHOOT MERISTEMLESS ( STM ) and WUS (Chen et al., 2010; Yang et al., 2013). The same set of genes is de‐repressed in val1/2 ( vp1/abi3‐like 1/2 ) double mutants, which also fail to form true leaves and develop embryo‐like proliferations in the root and shoot apical meristem regions (Suzuki, Wang, & McCarty, 2007; Yang et al., 2013). VAL1 and VAL2 are B3 domain TFs, as are the SE inducers ABI3, FUS3, and LEC2, but the VAL proteins also possess CW and PHD domains that can associate with chromatin factors (Suzuki et al., 2007).…”
Section: The Role Of Chromatin Modifications In Somatic Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype is associated with upregulation of LAFL gene expression, as well as ectopic expression of the stem cell regulators WUSCHEL RELATED HOMEOBOX 5 ( WOX5) , BBM , SHOOT MERISTEMLESS ( STM ) and WUS (Chen et al., 2010; Yang et al., 2013). The same set of genes is de‐repressed in val1/2 ( vp1/abi3‐like 1/2 ) double mutants, which also fail to form true leaves and develop embryo‐like proliferations in the root and shoot apical meristem regions (Suzuki, Wang, & McCarty, 2007; Yang et al., 2013). VAL1 and VAL2 are B3 domain TFs, as are the SE inducers ABI3, FUS3, and LEC2, but the VAL proteins also possess CW and PHD domains that can associate with chromatin factors (Suzuki et al., 2007).…”
Section: The Role Of Chromatin Modifications In Somatic Embryogenesismentioning
confidence: 99%
“…The same set of genes is de‐repressed in val1/2 ( vp1/abi3‐like 1/2 ) double mutants, which also fail to form true leaves and develop embryo‐like proliferations in the root and shoot apical meristem regions (Suzuki, Wang, & McCarty, 2007; Yang et al., 2013). VAL1 and VAL2 are B3 domain TFs, as are the SE inducers ABI3, FUS3, and LEC2, but the VAL proteins also possess CW and PHD domains that can associate with chromatin factors (Suzuki et al., 2007). VAL proteins are required for PRC1‐mediated deposition of H2Aub at seed maturation genes and BBM (Yang et al., 2013).…”
Section: The Role Of Chromatin Modifications In Somatic Embryogenesismentioning
confidence: 99%
“…The VP1/ ABI3-LIKE (VAL) proteins are a class of B3 domain proteins with a possible chromatin-related repressor function. Double val1 val2 or val1 val3 mutants and single val1 mutants treated with GA biosynthesis inhibitors develop embryonic characteristics on seedlings, a phenotype that correlates with derepression of LEC1 and other genes encoding embryo-expressed B3 domain factors (Suzuki et al 2007). The WUSCHEL (WUS) homeodomain protein specifies stem cell fate in the shoot and floral meristem (Laux et al 1996;Mayer et al 1998), but also promotes somatic embryo development in seedlings when ectopically expressed (Zuo et al 2002;Gallois et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Because CHD3 proteins are involved in transcriptional repression, PKL has been proposed to prevent re-expression of the embryonic developmental state during germination, likely through the regulation of gibberellin (GA) signaling [10,11]. A more recent study identified three functionally redundant VP1/ ABI3-LIKE (VAL) genes encoding B3 domain-containing proteins [12]. Whereas val1 shows a pkl-like phenotype, the val1 val2 double mutant produces embryo-like structures around root and apical meristem regions, which is associated with increased expression of LEC1, L1L, ABI3, and FUSCA3 (FUS3).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas val1 shows a pkl-like phenotype, the val1 val2 double mutant produces embryo-like structures around root and apical meristem regions, which is associated with increased expression of LEC1, L1L, ABI3, and FUSCA3 (FUS3). It has been proposed that VAL factors may function as transcriptional repressors of the LEC1/B3 genes in conjunction with PKL or related factors [12].…”
Section: Introductionmentioning
confidence: 99%